COVID is fake; it’s a plandemic: a case study on the motivations of Filipino COVID-19 deniers’ information-seeking behavior - Buenavista, Ces Archae D.
The contamination brought by COVID-19 also spread in the information sphere through the infodemic brought by the spikes of information disorders during the pandemic, such as conspiracy theories proclaiming that COVID is fake; it is all planned, a plandemic. Due to an encounter with a COVID-19 denier, the researcher was inspired to explore the factors motivating the information-seeking behavior of Filipino COVID-19 deniers.